2015
DOI: 10.1002/anie.201500191
|View full text |Cite
|
Sign up to set email alerts
|

Microscale Crystals of Cytochrome c and Calixarene on Electrodes: Interprotein Electron Transfer between Defined Sites

Abstract: The assembly of redox proteins on electrodes is an important step in biosensor development. Recently, p-sulfonato-calix[4]arene was shown to act as "molecular glue" for the assembly and crystallization of cytochrome c (cyt c). Electrochemical data are presented for microscale cyt c-calixarene crystals grown on self-assembled monolayers (SAM)-modified Au electrodes. The crystals were characterized by cyclic voltammetry and exceptionally high concentrations of electroactive cyt c were obtained. The peak currents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…Interestingly, recent studies have shown that in calixarene-supported cyt c crystals ET between fixed redox sites is feasible. 54 …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, recent studies have shown that in calixarene-supported cyt c crystals ET between fixed redox sites is feasible. 54 …”
Section: Resultsmentioning
confidence: 99%
“…Examples include the use of calixarenes, cucurbiturils, foldamers, and fullerene (C 60 ) . The water‐soluble p ‐sulfonatocalix[4]arene (sclx 4 ) is a versatile receptor for cationic side chains and serves as molecular glue for protein assembly . Previously, it was shown by X‐ray crystallography that three sclx 4 molecules bind to different lysines on cytochrome c (cyt c ) .…”
Section: Figurementioning
confidence: 99%
“…The regulation of protein assembly and disassembly mediated by soluble derivatives and based on rational supramolecular approaches has known a growing interest the last decades. 1,2 Indeed, these molecular glues, such as lanthanide coordination complex 3,4 , polyoxometalate clusters 5,6 or organic supramolecular compounds, [7][8][9][10][11] favor protein/additive/protein adduct to create protein material 12 or induce protein crystallization. 13 In that realm, functionalized calixarenes, notably para-sulfonato-calix-[n]-arenes have demonstrated their high potential in biochemistry thanks to their abilities to bind positively charged protein surface to form protein oligomers.…”
Section: Introductionmentioning
confidence: 99%